2007
DOI: 10.1073/pnas.0709506104
|View full text |Cite
|
Sign up to set email alerts
|

Phorbol ester stimulation of RasGRP1 regulates the sodium-chloride cotransporter by a PKC-independent pathway

Abstract: The sodium-chloride cotransporter (NCC) is the principal salt-absorptive pathway in the mammalian distal convoluted tubule (DCT) and is the site of action of one of the most effective classes of antihypertensive medications, thiazide diuretics. We developed a cell model system to assess NCC function in a mammalian cell line that natively expresses NCC, the mouse DCT (mDCT) cell line. We used this system to study the complex regulation of NCC by the phorbol ester (PE) 12-O-tetradecanoylphorbol-13-acetate (TPA),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 37 publications
3
52
0
Order By: Relevance
“…A recent study also showed that WNK4 increases the association of NCC with AP3 to promote NCC delivery to the lysosomal compartment for degradation, 40 which is consistent with our conclusion. Our findings further support the notion that NCC is regulated through affecting its forward trafficking in addition to other mechanisms such as altering its abundance, [41][42][43] glycosylation, 10 and phosphorylation. 44,45 In the kidney, NCC is exclusively expressed in DCT and responsible for 5 to 7% of sodium reabsorption.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…A recent study also showed that WNK4 increases the association of NCC with AP3 to promote NCC delivery to the lysosomal compartment for degradation, 40 which is consistent with our conclusion. Our findings further support the notion that NCC is regulated through affecting its forward trafficking in addition to other mechanisms such as altering its abundance, [41][42][43] glycosylation, 10 and phosphorylation. 44,45 In the kidney, NCC is exclusively expressed in DCT and responsible for 5 to 7% of sodium reabsorption.…”
Section: Discussionsupporting
confidence: 77%
“…46 It is likely that, under normal physiologic conditions, NCC constantly traffics to both the plasma membrane via a secretory pathway and the lysosome for degradation to maintain its basal steady protein level, which is subject to regulation by many mediators. 3,6,10,[41][42][43][44][45] Renal DCT cells contain endogenous WNK4 kinase. 2 In the presence of WNK4, the rate of NCC targeting to the lysosomal compartment is much higher than that of NCC without WNK4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One example is the regulation of NCC by phorbol esters [54]. This 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 12 effect is mediated through Ras guanyl-releasing protein 1 and ERK1/2, which stimulates ubiquitylation and endocytosis of NCC [55].…”
Section: Other Signaling Moleculesmentioning
confidence: 99%
“…A WNK4-induced decrease in NCC membrane abundance has been shown to occur via alteration of NCC forward trafficking (exocytosis) (10,11). Ko et al (12,13) demonstrated that treatment of DCT cells with the phorbol ester 12-O-tetradecanoyl-phorbol-13-acetate reduced NCC membrane abundance via a Ras-GRP1 (Ras-guanyl nucleotide-releasing protein 1)-dependent ERK1/2-MAPK pathway (12) that increased ubiquitylation and dynamin-dependent internalization of NCC (13). However, the exact mechanisms behind the regulated endocytosis of NCC and whether, similarly to the water channel aquaporin 2 (AQP2) (14) and the sodium potassium chloride cotransporter NKCC2 (15), constitutive endocytosis of NCC plays a role in steady-state surface expression of NCC are not known.…”
mentioning
confidence: 99%